Ch. 249, Subchapter 8-Crimes against the Public Peace, §§ 307-308-Aiming or Discharging Firearms & Use of Firearms by Minor, in Session Laws of the State of Washington Eleventh Session (1909). - (:unkn) unknown (My University, 1909)
Every person who shall aim any gun, pistol, revolver or other firearm, whether loaded or not, at or towards any human being, or who shall wilfully discharge any firearm, air gun or other weapon, or throw any deadly missile in a public place, or in any place where any person might be endangered thereby, although no injury result, shall be guilty of a misdemeanor.No minor under the age of fourteen years shall handle or have in his possession or under his control, except while accompanied by or under the immediate charge of his parent or guardian, any firearm of any kind for hunting or target practice or for other purposes. Every person violating any of the foregoing provisions, or aiding or knowingly permitting any such minor to violate the same, shall be guilty of a misdemeanor."
Keywords: BRANDISHING; POSSESSION - MINORS